TEXTURE AND ORGANOLEPTIC PROFILES OF BROILER MEATS FROM RAISING SYTEMS IN A CLOSED HOUSE - I N. S., MIWADA; SUKADA, I K.; ARIANA, I N. T. (Majalah Ilmiah Peternakan; Vol 25 No 3 (2022): Vol. 25 No. 3 (2022), 2022)
The purpose of this study was to characterize the stock of broiler meat sourced from the cage maintenance sys- tem, especially related to mass quality at room temperature. The quality indicators observed included texture and organoleptic profiles of broiler chicken meat. The research methodology used a completely randomized design with 4 shelf-life treatments (S), namely S1 (1 hour); S2(3hours); S3 (5 hours) and S4 (7 hours). The results showed that the characteristics of broiler meat sourced from the rearing system in the cage gave a significantly different profile of meat texture, especially on the level of meat hardness during different storage times. However, the springeness, cohesiveness and gumminess values were not affected by the treatment. L* decreased with the shelf life of the value, but at 7 hours of storage there was an increase in the value of L*. While the value of a* at 7 hours of storage showed the highest value achieved from the increase in meat color as a result of dehydration on the surface of the meat. While the value of b* indicates an increase in meat color during storage at room temperature. Organoleptic aspects such as color, texture, taste, and total acceptance did not change during storage, except for the aroma aspect. The conclusion of the research is that the broiler chicken products that are carried out come from a closed house mainte- nance system if storage at room temperature does not change the profile texture, such as springeness, cohesiveness and gumminess, except for the hardness value. Overall, the organoleptic value was responded the same by consu- mers, except for the aroma at 7 hours of storage (S4).